Mutilating predation in the Cheirodontinae Odontostilbe pequira (Characiformes: Characidae) - Lima, Monise R.L.; Bessa, Eduardo [UNESP]; Krinski, Diones; Carvalho, Lucélia Nobre (FapUNIFESP (SciELO), 2012)
We observed individuals of Odontostilbe pequira, a small characid, approaching and biting individuals of larger-bodied fishes of other species. This observation was made in two clear water headwater streams of the Cuiabá basin, Paraguay River system, located in Nobres, Mato Grosso State, Brazil, which led us to investigate the behavioral interactions of these fish. We characterized behavioral interactions between species by direct underwater observations using snorkelling and video recordings. Additionally, we proceeded diet analyses of O. pequira, obtaining intestinal coefficient and the index of alimentary importance. During underwater observations we checked the relative frequency of attacks by O. pequira on larger fish species. Odontostilbe pequira attacked individually or in large groups, and the anostomid Leporinus friderici was the preferred target prey species, while Prochilodus lineatus was apparently avoided. Our study sustains that O. pequira is omnivorous, with a diet that varies seasonally. It feeds mainly on plants, but also on animal prey, including the scales of small fishes, and, possibly, the mucus and epidermis of larger fish species. We suggest the term mutilating predation to describe the latter relationship. © 2012 Sociedade Brasileira de Ictiologia.
Keywords: Animal behavior; Feeding plasticity; Lepidophagy; Underwater observations